Gaston Bachelard's Epistemology: عند غاستون باشلار (Journal of Academic Research, 2024)
This research Gaston Bachelard's Epistemology delves into a vital issue that stands as a key characteristic in contemporary philosophical thought—the epistemology, as conceptualized by Gaston Bachelard. The study presents Bachelard's philosophical views on epistemology, focusing on his exploration of the field's significance in science. Bachelard contends that traditional philosophies have become obsolete by neglecting contemporary scientific revolutions and their impact on cognitive values. Thus.